Historical Literacy in Social Studies Learning at Junior High School: Analysis of Implementation and Challenges - Uun Lionar; Nana Supriatna; Agus Mulyana; Murdiyah Winarti; M Maman Sumaludin; Yelda Syafrina (Indonesian Journal of Social Science Education (IJSSE), 2024)
Historical literacy is crucial in the teaching of social studies to enhance students' understanding of historical aspects. In this research, an analysis was conducted regarding the implementation of historical literacy development in social studies teaching at Junior High Schools in Bandung City. The research method used was qualitative descriptive to identify the efforts of historical literacy development by teachers and to identify the challenges faced. Data was obtained through observations and interviews with teachers and students at Kartika XIX-2 Junior High School in Bandung City. The results of the research indicate that teachers have been developing historical literacy through classroom activities focusing on historical investigation, historical writing, and the development of historical understanding. However, some challenges persist, such as low student participation, time constraints within the social studies curriculum, and the need for improvement in teachers' pedagogical skills. To enhance historical literacy in the future, it is recommended to utilize technology, develop contextual teaching materials, and implement a multiliteracy learning approach. Thus, it is hoped that students can be more active and critical in understanding social studies subjects with a relevant historical context to contemporary life. This research has implications for the development of social studies curriculum in the future to pay more attention to integrating historical literacy as an integral part of social studies learning.